P65 Adjuvant management of operated uterine sarcomas: a single institution experience. (1st November 2019) - Cordoba, A; Prades, J; Basson, L; Robin, Y-M; Taieb, S; Narducci, F; Hudry, D; Bresson, L; Chevalier, A; Le Tinier, F; Mirabel, X; Lartigau, E; et al.
Abstract : Introduction/Background: Describe the adjuvant management of high grade Uterine Sarcoma (US) and highlight prognostic factors for overall survival (OS) and pelvic-free survival (PFS). Methodology: Between 01/2000 and 01/2015, 91 patients undergoing surgery were presented at the Multidisciplinary Team Meeting of our institution. The type of surgery, the anatomopathological features, adjuvant treatments, dates and sites of recurrence were collected. The prognostic value of the various factors was evaluated with the multivariate Cox model. Results: A total of 50 women were identified including 43 (86%) leiomyosarcomas and 7 (14%) high grade sarcoma. 18 (36%) patients received adjuvant pelvic radiotherapy (AR) and 6 (12%%) received adjuvant systemic therapy. The median follow-up time was 63 months. 39 (78%) patients had a recurrence: 22 (58%) only metastatic recurrence, 2 (5%) isolated pelvic recurrence and 15 (38%) pelvic and metastatic recurrence. AR (p=0.005, HR=0, 15) was associated with survival without pelvic recurrence in univariate analysis; age >55 years (p=0.015, HR=2.37) and AR (p=0.013, HR=0.41) were associated with metastatic free survival in multivariate analysis. Conclusion: According to the results of our series, there is a benefit of radiotherapy after surgery in terms of local control of US. It is necessary to identify the subgroup of patients who will benefit from an AR in order to provide them with more optimal care. Disclosure: The authors declare that they have no potential conflict of interest relevant to this article.